Odontogenic sinusitis: A state‐of‐the‐art review. Issue 1 (22nd March 2022) - Craig, John R.
Abstract: Odontogenic sinusitis (ODS) is more common than historically reported, and is underrepresented in the sinusitis literature. ODS is distinct from rhinosinusitis in that it is infectious sinusitis from an infectious dental source or a complication from dental procedures, and most commonly presents unilaterally. ODS clinical features, microbiology, and diagnostic and treatment paradigms are also distinct from rhinosinusitis. ODS evaluation and management should generally be conducted by both otolaryngologists and dental providers, and clinicians must be able to suspect and confirm the condition. ODS suspicion is driven by certain clinical features like unilateral maxillary sinus opacification on computed tomography, overt maxillary dental pathology on computed tomography, unilateral middle meatal purulence on nasal endoscopy, foul smell, and odontogenic bacteria in sinus cultures. Otolaryngologists should confirm the sinusitis through nasal endoscopy by assessing for middle meatal purulence, edema, or polyps. Dental providers should confirm dental pathology through appropriate examinations and imaging. Once ODS is confirmed, a multidisciplinary shared decision‐making process should ensue to discuss risks and benefits of the timing and different types of dental and sinus surgical interventions. Oral antibiotics are generally ineffective at resolving ODS, especially when there is treatable dental pathology. When both the dental pathology and sinusitis are addressed, resolution can be expected in 90%–100% of cases. For treatable dental pathology, while primary dental treatment may resolve the sinusitis, a significant percentage of patients still require endoscopic sinus surgery. For patients with significant sinusitis symptom burdens, primary endoscopic sinus surgery is an option to resolve symptoms faster, followed by appropriate dental management. More well‐designed studies are necessary across all areas of ODS. Abstract : Odontogenic sinusitis is a unique form of sinus disease requiring diagnostic and therapeutic approaches that are distinct from non‐odontogenic rhinosinusitis. This review will provide you with an up‐to‐date evidence‐based approach to managing odontogenic sinusitis. Highlights: Odontogenic sinusitis (ODS) is one of the most common cause of unilateral maxillary sinus disease, but has been underrepresented in previous sinusitis literature. Clinicians must be able to suspect ODS based on certain clinical features like unilateral middle meatal purulence on nasal endoscopy, subjective foul smell, and sinus computed tomography demonstrating maxillary sinus opacification with or without overt adjacent dental pathology. Diagnosing ODS requires confirmation of infectious sinusitis by otolaryngologists ideally with nasal endoscopy, and confirmation of adjacent maxillary dental pathology by dental specialists. Management centers on multidisciplinary collaboration and shared‐decision making between otolaryngologists, dental specialists, and patients.